Преобразуйте в многочлен выражение
1) (-m+n)^3
2) (-2+k)^3
3) (-x-y)^3
4) (-0.5+p)^3

  • 1) (-m+n)^3 = (n-m)^3
    Вспоминаем формулу сокращенного умножения:
    (a-b)^3 = a^3 - 3a^2b + 3ab^2 - b^3
    Получаем:
    n^3 - 3n^2m + 3nm^2 - m^3

    2) (-2+k)^3 = (k-2)^3 
    Вспоминаем формулу сокращенного умножения:
    (a-b)^3 = a^3 - 3a^2b + 3ab^2 - b^3
    Получаем:
    k^3 - 3k^2 * 2 + 3k * 2^2 - 2^3 = k^3 - 6k^2 + 12k - 8

    3) (-x-y)^3 = -(x+y)^3
    Вспоминаем формулу сокращенного умножения:
    (a+b)^3 = a^3 + 3a^2b + 3ab^2 + b^3
    Получаем:
    (-x-y)^3 = -((x+y)^3) = -(x^3 + 3x^2y + 3xy^2 + y^3) = 
    = -x^3 - 3x^2y - 3xy^2 - y^3

    4) (-0.5+p)^3 = (p-0.5)^3
    Вспоминаем формулу сокращенного умножения:
    (a-b)^3 = a^3 - 3a^2b + 3ab^2 - b^3
    Получаем:
    p^3 - 0,5p^2 + 0,25p - 0,125 


See also: